2011
DOI: 10.1007/s11661-011-0724-x
|View full text |Cite
|
Sign up to set email alerts
|

Structural Transitions and Magnetic Properties of Ni50Mn36.7In13.3 Particles with Amorphous-Like Phase

Abstract: The high-energy ball-milling method was used for fabricating Ni 50 Mn 36.7 In 13.3 fine-sized particles. The as-melt polycrystalline Ni 50 Mn 36.7 In 13.3 alloy exhibits a 14 M modulated martensite structure at room temperature (RT). The atomic pair distribution function analysis together with the differential scanning calorimetry technique proved that the 14 M modulated martensite transformed to a metastable amorphous-like structure after ball milling for 8 hours. Annealing of the ball-milled particles with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The significant broadening of the main reflection (at approximately 43° 2θ— Figure 2 ) indicates that the as-milled powder consists of a mixture of amorphous (or strongly refined nanocrystalline—peak 1) and bcc (peak 2) which have been identified as “the amorphous-like phase” [ 23 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The significant broadening of the main reflection (at approximately 43° 2θ— Figure 2 ) indicates that the as-milled powder consists of a mixture of amorphous (or strongly refined nanocrystalline—peak 1) and bcc (peak 2) which have been identified as “the amorphous-like phase” [ 23 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is due to the lattice distortion of the parent phase and L2 1 growth. Liu et al [ 23 ] observed a tetragonally distorted Heusler phase in Ni 50 Mn 36.7 In 13.3 powders annealed for 30 min at 411 °C (684 K). The activation energies (E a ) determined for studied Ni 45.5 Co 4.5 Mn 36.6 In 13.4 MA alloys are similar to those observed for other magnetic shape memory powders obtained by high-energy-ball-milling (e.g., Ni-Mn-Ga and Ni-Mn-In) and slightly higher than for NiMn-based films obtained by magnetron sputtering.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous results, which allow to control the microstructure of the alloy and its influence on the magnetic behavior, are in full agreement with behaviors observed in similar alloy systems. Nevertheless, the possible spin glass behavior linked to the amorphous state (proposed in a similar Ni-Mn-In alloy [26]) and the evolution of magnetism brought by the crystallization process needs to be analyzed in more detail. In this sense, magnetization and susceptibility measurements has been performed on the milled samples.…”
Section: Resultsmentioning
confidence: 99%
“…For the case of the metamagnetic alloys, this effect has been scarcely analyzed in the bibliography. As in NiMnGa powders, the austenitic phase is obtained only after heating up to high temperatures in NiMnSn (1223 K) [25] and NiMnIn particles (673 K) [26]. In this latter case, a magnetic transition from paramagnetic-like to spin-glass state is suggested to occur at low temperatures as a consequence of the induced defects.…”
Section: Introductionmentioning
confidence: 95%